Environmental conservation in Bhutan: Organization and policy - Kaewkhunok, Suppawit (ASIAN REVIEW, 2018)
This article is about Bhutan's success in conserving natural resources and the environment through its organizational and public policy perspectives. At the same time, it analyses the weaknesses and strengths of Bhutan's policy and organizational management in environmental conservation. The integration of the sustainable development approach and the Mahayana Buddhism philosophy has led to the creation of the Gross National Happiness (GNH) which is an important concept that drives the Bhutan government to pay more attention to environmental protection. The close relationship between the Bhutanese and the environment is in accordance with the old beliefs and the influence of Buddhism has contributed to the successful implementation of the government's environmental policy. In addition, the driving force behind the environmental policy has been to design an organizational structure that promotes public participation in order to truly reflect the problem and contribute to sustainable solutions. Integrating indigenous ideas with international principles and building public participation, which indicates Bhutan's success in driving environmental policy, is an important finding of this work.